The assessment of the relationship between various waterscapes and outdoor activities: Edirne, Turkey - Sakıcı, Çiğdem (Springer Science and Business Media LLC, 2014)
The environment is very important in terms of the behaviours and actions of human beings, and activity-environment correlation is used frequently in outdoor arrangements. The environment must meet the requirements and expectations of society. Outdoor activities are the activities that contribute to the well-being of human beings in physical (heartbeat, respiration, blood pressure, etc.) (Ulrich, Journal of Environmental Psychology 11:210-230, 1991), psychological (fear, anxiety, depression, loneliness, stress, etc.) (Marcus and Barnes 1999) and behavioural (insomnia, nervousness, restlessness, passivity, etc.) (Ulrich 1999) terms. It is known that human beings are affected significantly by the environments they are in, and more importantly, it is known that the environment they are in affects their happiness status. The causes of this effect are the features and appearances of the spatial elements and components that mainly make up such environments. One of the elements that is used frequently in landscape is water. If one examines designed or natural open spaces, it may be observed that water has very distinctive features. Dynamic (in the form of a leak, with intense flow rate, cascade, foamy, squirting, jet, graded, etc.) and still water elements may be used with sculptures, plants, rocks and elevations (on land). This study aims to reveal which age groups of students enjoy the different types of activities with regards to water features and emotional associations that motion and characteristics of water bring out in human beings and also to reveal the water preferences of human beings, including their reasons for such preference. Thus, 20 different water compositions located in Edirne Province were selected, and in 2-min camera reels, the students of various age groups assessed water with various characteristic features via a survey. As a result, it was revealed that human beings from various age groups wish to perform different activities with water elements having distinctive characteristic features, and the types of water elements that are subject to various age groups' like and dislike were determined. Kruskal-Wallis test was used during testing the effect of age differences. Chi-square analysis was used in order to examine the effect of age differences on preferences with regards to the activities that shall be performed at locations that include utilization of various water elements. The results reveal that while the use of water should be allowed in landscaping, selections regarding the elements of these water features should be made based on the type of activity and the age group of users in relation to the location.
Keywords: Turkey; Water Supply; Humans; Recreation; Perception; Environmental Monitoring; 13. Climate action; 16. Peace & justice